Optımızatıon Of Employee Performance Of Regıonal Technıcal Implementatıon Unıts To Expedıte Shıp Departure Actıvıtıes - Evada Rustina; Nur Wening; Wahyu Suwaldi; Sumarwanto Sumarwanto (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to optimize the performance of employees of the Regional Technical Implementation Unit (UPTD) at the Kendal Crossing Port and find out the departure process of KMP Kalibodri Semarang at the Kendal Crossing Port. The research method uses a qualitative method approach. Data were analyzed by interviews, observations, documentation studies and literature studies. The results showed that the main objective of UPTD Kendal Crossing Port is to ensure efficient, safe, and appropriate port operations to the needs of port users and maintain the sustainability of port development. How to optimize the performance of UPTD employees at Kendal Crossing Port includes coordination, supervision, arrangement of transportation modes, and promotion.